Heterologous production of recombinant peptidylglycine α-amidating monooxygenase for the production of biosimilar α-amidated peptides - Morrison, David Graham (Department of Clinical Laboratory Sciences, 2022)
A biological method for peptide synthesis provides increased production capacity of inexpensive peptide pharmaceuticals with environmentally safe procedures relative to current chemical peptide synthesis. Most precursor peptides are readily produced from yeast and bacterial systems using recombinant DNA technologies but require C-terminal amidation for maximum biological activity. Peptidylglycine α-amidating monooxygenase (PAM) is the only enzyme that catalyses the C-terminal amidation of peptides in vivo through its two catalytic cores, peptidylglycine α-hydroxylating monooxygenase (PHM) and peptidylglycine αamidating lyase (PAL). The cost and limited quantities of the commercial PAM variants available have necessitated research into low cost, scalable quantities of PAM and peptide amidation to enable inexpensive biological peptide production. In the present study, an assay for measuring the product of PAM activity, glyoxylate, was developed based on a 2-aminobenzaldehyde-glycine-glyoxylate (AGG) absorbance assay. The AGG chromophore synthesised was identified with ultra-performance liquid chromatography mass-spectroscopy (UPLC-MS). PAM activity was measurable with glyoxylate between 25 µM and 1600 µM with the AGG assay. Furthermore, the activity of PHM alone was measured by the inclusion of an alkaline hydrolysis step to lyse glyoxylate as a substitute for PAL catalytic activity. Multiple candidate proteins and DNA sequences for PAM were identified by genetic sequence searches and a novel fungal PHM modelled in silico. Fourteen PAM, PHM, PAL and truncated constructs were expressed in the non-conventional yeast host, Yarrowia lipolytica. The novel fungal PHM's nutrient, temperature, and pH conditions were optimised to maximise protein expression. Enzyme purification was optimised with scalable industrial appropriate methods to purify milligram amounts of fungal PHM. The AGG assay was validated with a commercially obtained PAM, demonstrating a simple medium-throughput method to measure PAM activity. The novel fungal PHM was characterised with a pH optimum of 4.0 and maximum enzymatic activity at 45°C. Deglycosylation of fungal PHM enhanced enzyme activity by 1.83 fold, but lowered the temperature optimum to 37°C. The novel PHM and alkaline hydrolysis catalysed the conversion of the peptide pharmaceutical precursor for exenatide into its final bioactive form.